Reconceptualizing English language learning resilience from positive psychology: scale development and psychometric validation - Yin, Ting; Chen, Jiexin; Lin, Zhiqing (Frontiers in Psychology, 2025)
BackgroundResilience, a central construct in positive psychology, plays a crucial role in helping language learners cope with and grow from the challenges inherent in English language learning. However, few systematically validated instruments are available to assess resilience within this specific context. To address this gap, the present study developed and validated the English Language Learning Resilience Scale.MethodsData were collected from 617 Chinese university students. The internal structure of the scale was examined through exploratory and confirmatory factor analyses, followed by measurement invariance testing. Additionally, the graded response model was applied to evaluate the psychometric properties of individual items.ResultsResults of factor analysis identified five protective factors—value, perseverance, emotion regulation, social support, and self-efficacy—demonstrating satisfactory convergent and discriminant validity. Furthermore, the scale showed scalar measurement invariance across gender, age, and academic discipline, indicating its structural stability across diverse subgroups. Complementing these findings, item response theory analyses provided additional evidence of strong item discrimination, appropriate difficulty parameters, and high measurement precision.ConclusionTheoretically, the study reconceptualizes resilience in language learning through the lens of positive psychology, offering a more nuanced understanding of its dimensions and functions. Practically, the scale offers educators a diagnostic tool for identifying learners with lower resilience and implementing targeted interventions to strengthen their capacity to adapt, persist, and thrive in the face of linguistic challenges, thereby promoting both their language learning success and overall psychological well-being.